European integration of the systems of higher education of Belarus and Armenia - Titarenko, Larissa G.; Zaslavskaya, Maria I. (Journal of the Belarusian State University. Sociology, 2019)
The paper is focused on the processes of integration of the systems of higher education in the Republic of Belarus and Republic of Armenia into the European educational space. The aim of the article is the comparative analysis of the present results of these processes reached by two countries. This analysis revealed some common problems and difficulties in the European integration of these two countries, regardless of the fact that Armenia joint the European educational space in 2005 while Belarus joint only in 2015. Both systems of higher education cannot completely accept the rules imposed by European educational space, as they want to keep their own national educational priorities and get the benefits from the European integration. The research results show that that any educational unions are becoming today a political tool, therefore joining the European educational space without adapting its principles to the socio-historical specifics of each country does not contribute to a practical increase in competitiveness of higher education systems in Armenia and Belarus and does not improve the quality of education. The obtained results demonstrate the new (European) status of the higher education systems of the two post-Soviet republics, not supported by the growth of exports of their educational services or by a visible improvement in the quality of education.